Adoption of Small-Scale Irrigation and Its impact on Household’s Income in Dugda Districts, East Shewa Zone, Oromia, Ethiopia - Mulatu, Gemechu (PT. Maju Malaqbi Makkarana, 2023)
The major of this study was to estimate the impact of Adoption of Small-Scale Irrigation in Dugda district. Data were collected from both primary and secondary data sources. Primary data was collected from 384 household heads in four kebeles of the district using structured questionnaire. Descriptive, logit and propensity score matching techniques were used for data analysis. The study finding from the propensity score matching technique revealed that the incomes of adopters of small scale irrigation were increased by 37,696.06ETB per annum. This calls for strengthening the available irrigation facilities and expansion of irrigation sector in the study area.